Arc welding control - Pan, Jiluan, 1927- (Woodhead Publishing series in welding and other joining technologies., 2003)
This book examines recent developments in modern arc welding. The book is essentially divided into five main parts. The first part gives an account of the dynamic behaviour of the arc, its power sources and its effect on welding technology. Part 2 then goes on to describe ways of controlling the welding arc through modern electronics, covering unique and original methods. The third part looks at the prospects of the arc sensor for automatic seam tracking in arc welding, and establishes the first mathematical model of the sensor on the basis of control theory. Part 4 describes an original new m.